Is Negation Negative? (And a Discussion of Negative Concord in SOV Languages) - Paloma Jeretič (Languages, 2025)
Is negation negative? For some authors, in some languages, it is not. This is the case for so-called strict negative concord languages (e.g., Russian), in which negation is taken to be non-negative, following the cross-linguistic analysis for negative concord systems proposed by Hedde Zeijlstra’s work “Sentential negation and negative concord”. However, this analysis is focused on languages with SVO word order. In this paper, I propose to reconsider the typology of negative concord by zooming out of the focus on SVO languages that current literature has relied on. I discuss the case of SOV languages where observing a strict NC pattern leads to weaker conclusions about the nature of negation than for SVO languages with strict negative concord, leaving the negativity status of negation in those languages underdetermined. I then take a look at Turkish, an SOV language with three sentential negation markers: plain sentential negation -mA, copular negation değil, and existential negation yok. Evidence from the interaction of these markers with neither..nor phrases suggests that değil and yok, in contrast with -mA, are non-negative for some speakers. In order to explain the variation, I put forward a hypothesis about the learning process, in which there is sometimes insufficient evidence in the input to determine whether değil and yok are negative, and learners choose between two conflicting heuristics that result in the negativity or non-negativity of these markers.